Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.5005/jp-journals-10005-1335
|View full text |Cite
|
Sign up to set email alerts
|

Awareness in Primary School Teachers regarding Traumatic Dental Injuries in Children and Their Emergency Management: A Survey in South Jaipur

Abstract: Introduction: Trauma to primary and permanent teeth and their supporting structures is one of the most common dental problems seen in children. The prognosis of traumatized teeth depends on timely attention with prompt and appropriate treatment, which often relies on knowledge of the teachers who may be present at the place of accidents. Thus, the aim of this study was to evaluate via a questionnaire the knowledge level of primary school teachers in South Jaipur regarding dental trauma.Design: Questionnaire su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 19 publications
3
19
0
4
Order By: Relevance
“…The study aimed to measure the knowledge and evaluate the ability of primary school teachers regarding dental injuries at school. As the child spends most of his day at school, and that involves running, playing, and accident falling, increasing the chance of dental injuries [5]. So the responsibility of the teachers to deal with the situation is of crucial importance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study aimed to measure the knowledge and evaluate the ability of primary school teachers regarding dental injuries at school. As the child spends most of his day at school, and that involves running, playing, and accident falling, increasing the chance of dental injuries [5]. So the responsibility of the teachers to deal with the situation is of crucial importance.…”
Section: Discussionmentioning
confidence: 99%
“…In Riyadh city, the percentage reached 22.7% out of 277 school teachers who at least have seen one dental trauma case throughout their career [7]. Another study conducted last year in South Jaipur, India, where only 31.8% out of 280 of school teachers faced a child dental trauma [5]. The high frequency of dental trauma among local primary school students showed the need to develop higher safety standards and more secured playfields and evaluate the teacher's knowledge regarding the management of dental trauma to determine the weak spots and suggest further research on how to improve it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First-aid provided by those present at the site of the traumatic incident, which includes school staff, is crucial, and immediate appropriate management plays an important role in the prognosis of injured teeth. 5 , 6 However, several studies conducted in different countries have reported that teachers, sports coaches, and school personnel, in general, lack adequate knowledge for managing dental trauma cases. 7 10 A similar lack of knowledge among school teachers has been reported in different Middle Eastern regions.…”
Section: Introductionmentioning
confidence: 99%
“…However, relatively similar findings were previously reported. In a study assessed through a questionnaire the knowledge level of primary school teachers regarding dental trauma, they reported that 31.8% of the participants had faced a dental trauma in a child [10]. Another study reported that 42.8% of the school teachers had seen conditions where a child's tooth was avulsed [11].…”
Section: Discussionmentioning
confidence: 99%